PENGARUH SERTIFIKASI HALAL, ENDORSEMET, DAN KUALITAS PRODUK TERHADAPKEPUTUSAN PEMBELIAN IPRODUK KOSMETIK WARDAH DI KOTA MATARAM - Putri Tasya, Dini; Sudiartha Athar, Handry; Herman Mulyono, Lalu Edy (Jurnal Magister Manajemen, 2023)
This istudy..aims ito..determine ithe iinfluence iof ihalal icertification, iendorsement iand.product iquality ion.consumer.decisions iin imaking ipurchases ion iWardah iCosmetic iProducts iin iMataram. iThis itype iof iresearch iuses iassociative iresearch iwith ia iquantitative iapproach. iThe idata icollection imethod iused iis ia isurvey isample imethod iwith idata icollected idirectly ifrom irespondents iusing iquestionnaires. iThe ipopulation iin ithis istudy iwas i90 iconsumers iwho ihad imade ipurchases ion iWardah iCosmetic iProducts. iSampling iusing inon iprobability iwith ipurposive isampling itechnique. iThe ianalytical itool iused iin ithis istudy iis iMultiple iLinear iRegression iAnalysis. iThe iresults iof ithis istudy ishow ithat ithere iis ia ipositive”and isignificant iinfluence ibetween iHalal iCertification, iEndorsement, iand iProduct iQuality ion iconsumer idecisions iin imaking ipurchases ion iWardah iCosmetic iProducts iin iMataram.